2015
DOI: 10.1016/j.jimonfin.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

ECB policy and Eurozone fragility: Was De Grauwe right?

Abstract: This is the other version of the paper.This version of the publication may differ from the final published version. Permanent repository link:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(10 citation statements)
references
References 21 publications
3
7
0
Order By: Relevance
“…Since the largest intensity of negative news concerning Spain was observed in the middle of 2010, in the autumn of 2011 and the first half of 2012, a significant increase in the volatility of shocks generated by Spain in these periods was in line with expectations. After the announcement about the OMT program by the European Central Bank in July 2012, the situation of the financial markets in the peripheral euro-area countries calmed down, which is in agreement with findings of other studies [40][41][42][43].…”
Section: Resultssupporting
confidence: 90%
“…Since the largest intensity of negative news concerning Spain was observed in the middle of 2010, in the autumn of 2011 and the first half of 2012, a significant increase in the volatility of shocks generated by Spain in these periods was in line with expectations. After the announcement about the OMT program by the European Central Bank in July 2012, the situation of the financial markets in the peripheral euro-area countries calmed down, which is in agreement with findings of other studies [40][41][42][43].…”
Section: Resultssupporting
confidence: 90%
“…The improvement in the sentiment in the government bond market of the euro area coincided with the announcement of the OMT programme. Similar conclusions can be drawn from the study by Saka et al (2015), who showed that market perception of overall euro area credit risk decreased under the OMT programme. Altavilla et al (2014) show that in the months following the announcement of the OMT programme, there was a decline in government bond yields, the overall situation in the financial markets improved, and the dependence of the euro area banking system on the Eurosystem's refinancing decreased.…”
Section: Literature Overviewsupporting
confidence: 87%
“…Long-term effects of the announcement of the OMT programme were, among others, confirmed in the studies of De Grauwe and Ji, 2014; Altavilla et al, 2014; 1 and Saka et al, 2015. As indicated by the first of these authors, a marked decline in government bond yields in the peripheral EMU countries since the third quarter of 2012 did not result from improving their macroeconomic fundamentals, but was determined by positive market sentiment.…”
Section: Literature Overviewmentioning
confidence: 71%
See 1 more Smart Citation
“…Shortly after Draghi's speech, on August 2, the Outright Monetary Transactions (OMT) framework was announced, which became operational on 6 September 2012. In the popular press it has been widely claimed that these actions have indeed calmed the Eurozone sovereign debt markets, a conclusion also supported, for example, by De Grauwe and Ji (2013) and Saka, Fuertes, and Kalotychou (2015).…”
Section: Introductionmentioning
confidence: 90%